Cancer-associated myositis associated with oesophageal adenocarcinoma arising in Barrett's oesophagus without serum myogenic enzymes elevation: an example suggesting the importance of MRI. (21st April 2016) - Sasaki, Yosuke; Shimizu, Hiroshige; Nemoto, Tetsuo; Urita, Yoshihisa
Abstract : The strong association between myositis and malignancy has been well recognised. Cancer-associated myositis (CAM) is thought to be a cross-reaction to regenerating muscle tissue similar to tumour antigen. We report a case of CAM due to oesophageal adenocarcinoma arising in Barrett's oesophagus without elevation of myogenic enzymes, diagnosed by MRI and repeated endoscopy. Elderly onset, prominent symptoms, lack of interstitial pneumonia, poorer response to immunosuppressive therapies, and the combination of negative conventional myositis-related antibodies and positive anti-p155/140 antibody may help to distinguish CAM from idiopathic inflammatory myopathy. As the prognosis of patients with CAM depends on the malignancy, aggressive diagnosis of CAM and the causative malignancy is required. Our experience underscores the importance of avoiding the over-reliance on serum myogenic enzymes for excluding CAM and recognising MRI as a useful diagnostic tool of myositis.